2023
DOI: 10.1017/jfm.2022.1014
|View full text |Cite
|
Sign up to set email alerts
|

Hypersonic flow over spherically blunted cone capsules for atmospheric entry. Part 2. Vibrational non-equilibrium effects

Abstract: Atmospheric entry capsules shaped as spherically blunted, large apex-angle cones are widely used in space missions. In Part 1 of this study (Hornung, Martinez Schramm & Hannemann, J. Fluid Mech., vol. 871, 2019, pp. 1097–1116) we explored flows over the two elements of the capsule shape, the sphere and the sharp cone with detached shock, theoretically and computationally. Using a large number of inviscid, perfect-gas computations, analytical functions of two independent variables, the normal-shock density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…At present there are many thermochemical non-equilibrium simulations on the aerothermodynamics of hypersonic re-entry vehicles (Sanderson et al 2004;Kim, Kang & Park 2020;Li et al 2021;Miró Miró et al 2021;Passiatore et al 2022;Wu et al 2022;Schramm, Hannemann & Hornung 2023). In these numerical studies, the thermal non-equilibrium effect was described by the multi-temperature energy equations (Zheng et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present there are many thermochemical non-equilibrium simulations on the aerothermodynamics of hypersonic re-entry vehicles (Sanderson et al 2004;Kim, Kang & Park 2020;Li et al 2021;Miró Miró et al 2021;Passiatore et al 2022;Wu et al 2022;Schramm, Hannemann & Hornung 2023). In these numerical studies, the thermal non-equilibrium effect was described by the multi-temperature energy equations (Zheng et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, compared with the conventional thermochemical non-equilibrium models, the collisional-radiative model can more reasonably predict the energy relaxation processes, chemical non-equilibrium and excited energy levels non-equilibrium phenomena. At present, the collisional-radiative model is usually implemented in zero-dimensional (0-D) (Teulet, Sarrette & Gomes 2001;Bultel et al 2006;Capitelli et al 2007;Annaloro & Bultel 2014) and one-dimensional (1-D) models (Panesi et al 2009;Campoli et al 2020;Du et al 2022), but has not been used in multi-dimensional flow calculations so far due to its intensive computational cost, and some simplification methods, such as the multi-group maximum entropy method, were proposed for simplifying the CR model for future coupling to multi-dimensional computational fluid dynamics (CFD) simulation (Liu et al 2015;Munafo, Liu & Panesi 2015;Munafo, Mansour & Panesi 2017;Sahai et al 2017Sahai et al , 2019Sahai et al , 2020Sharma, Liu & Panesi 2020). The 0-D calculations of the air collisional-radiative model for typical re-entry conditions indicated that the distributions of chemical species exhibit large differences from the results obtained by the global air chemical models (Bultel et al 2006;Annaloro & Bultel 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation